P24 The status of the liver in the adult fontan. (2nd March 2016) - Modhwadia, S; Jiang, J; Bowater, S; Hudsmith, L; Thorne, S; Clift, P
Abstract : Introduction: It is increasingly recognised that as Fontan survivors age there is an increasing prevalence late hepatic complications including abnormal hepatic function, fibrosis and cirrhosis and rarely hepatocellular carcinoma. 1, 2, 3 Just as corrective surgery for this cohort has considerably reduced childhood mortality, it is as equally important to avoid a premature death in adulthood. We describe the status of the liver in a large cohort of adults with the Fontan circulation. Methods: A retrospective review of case records and the liver investigations performed in all adult Fontan patients under review in our unit. We recorded individual liver function tests (LFTs), alpha fetoprotein levels, the results of liver ultrasound scans and presence of hepatocellular carcinoma. Where present, complications of liver disease such as ascites, jaundice and oesophageal varices were recorded. Results: 215 Fontan patients have been transitioned to adult care in our institution, mean age 28.2 ± 9.6 years, male 55%, time since Fontan surgery 19.8 ± 5.2 years, liver assessments had been made in 170 patients (79%), abnormal LFTs present in 49% of those tested and abnormal liver scans in 34%. Mean alanine transaminase level 27.4 ± 10.8 U/L, mean alkaline phosphatase level 105.4 ± 79.6 U/L, mean bilirubin 19 ± 17 umol/L and mean a fetoprotein level 2.6 ± 1.5 kU/L (normal range <6). There was one death related to hepatocellular carcinoma with known chronic liver disease. Ascites was present in 16 patients (7%) of which 5 had normal liver ultrasound scans. No patients had clinical evidence of oesophageal varices. 2 patients had a history of Gilbert syndrome with isolated raised bilirubin levels. Only 40% of patients with LFT abnormalities had abnormalities of their liver ultrasound and only 57% of those with abnormal scans have abnormal LFT findings. Discussion: Clinically relevant liver disease remains rare and occurs late after Fontan surgery. Only 79% of this cohort of adult Fontan patients had completed liver surveillance (LFT/liver ultrasound and alpha fetoprotein levels) suggesting improvements in liver surveillance are possible. However liver function tests did not predict outcome of liver ultrasound nor did liver ultrasound abnormalities predict abnormalities of the LFT. Improved liver surveillance is possible utilising non-invasive measures of liver function, such as the aspartate transaminase platelet ratio index (APRI), Fibroscan 4 and liver MRI. We are prospectively analysing liver status in adult Fontan patients using these techniques. References: Rychik J, Veldtman G, Rand E, et al. The Precarious State of the Liver After a Fontan Operation: Summary of a Multidisciplinary Symposium. Pediatric Cardiology. 2012;33(7):1001-1012 doi:10.1007/s00246-012-0315-7 Ghaferi AA, Hutchins GM. Progression of liver pathology in patients undergoing the Fontan procedure: chronic passive congestion, cardiac cirrhosis, hepatic adenoma, and hepatocellular carcinoma. J Thorac Cardiovasc Surg.2005;129:1348–1352 Asrani, Sumeet K., Carole A. Warnes, and Patrick S. Kamath. 'Hepatocellular Carcinoma After The Fontan Procedure'. New England Journal of Medicine 2013;368 (18):1756‑1757. Web. 24 Sept. 2015 Wai CT, Greenson JK, Fontana RJ, et al. A simple noninvasive index can predict both significant fibrosis and cirrhosis in patients with chronic hepatitis C. Hepatology 2003;38 :518e26